The impact of applying the total quality management model on the performance of the telecom organizations in Romania - Cristian Busu; Mihail Busu (Amfiteatru Economic Journal, 2017)
The present paper brings into discussion Edwards Deming's conceptualized model of Total Quality Management highlighting different phases within its evolution as it is seen in the economic literature. A temporal incursion allows a better understanding of the way quality standards implemented by means of total quality management programs are reflected in final consumer's satisfaction as well as in organizations' long-term performance. Conceptual development of the model is intertwined with the pragmatic side, by presenting a case study of the mobile telecommunication sector in Romania. The quantitative research analyzes the influence of total quality management's (TQM) implementation in achieving the competitive advantage and the performance of enterprises in the telecom sector. Data were collected by means of a survey through a questionnaire addressed to the respondents and the hypotheses of structural equation modeling (SEM) were tested by partial least squares path modeling (PLS). Data analysis was conducted by means of the statistical software SmartPLS 2.0 M3 software. The research conclusions confirm the theoretical issues presented throughout the paper, emphasizing the fact that enterprises' performance is the direct result of the collaboration between a series of factors such as the motivated workforce, decisional power quality as well as operational process integrity.
Keywords: C35; O32; L22; 330; total quality management; economic performance; final consumer's satisfaction; telecommunications; motivated workforce; integrated processes; quality of management